Pribumisasi Hadis di Nusantara: Studi atas Manuskrip Hikayat Nabi Mi’raj Koleksi Stattsbibliothek zu Berlin (Schoemann V 32) - Firdausy, Hilmy (Ushuluna: Jurnal Ilmu Ushuluddin, 2024)
This research examines the process of indigenization of hadith in the archipelago through analysis of the Hikayat Nabi Mi’raj manuscript in the collection of the Staatsbibliothek zu Berlin (Schoemann V 32). The main focus of the research is how the hadith narrative about the Isra' and Mi'raj was restructured and re-presented in the form of a saga, which became a medium for spreading Islamic traditions among grassroots society. The research results show that the saga not only reproduces the story of Isrā' and Mi'raj textually, but also enriches the narrative with local and cosmological elements that reflect the cultural context of the Indonesian people. This adaptation process involves developing the story structure, adding characters, and inserting local wisdom values that are relevant to the local audience. This research confirms that saga manuscripts have significance in understanding the dynamics of the spread of Islam and the formation of the collective imagination of the Indonesian Muslim community.